Differences in Left Ventricular Global Function and Mechanics in Paralympic Athletes with Cervical and Thoracic Spinal Cord Injuries - Currie, Katharine D.; West, Christopher R.; Krassioukov, Andrei V. (Frontiers in Physiology, 2016)
Following a spinal cord injury, there are changes in resting stroke volume (SV) and its response to exercise. The purpose of the following study was to characterize resting left ventricular structure, function and mechanics in Paralympic athletes with tetraplegia (TETRA) and paraplegia (PARA) in an attempt to understand whether the alterations in SV are attributable to inherent dysfunction in the left ventricle. This retrospective study compared Paralympic athletes with a traumatic, chronic (>1 year post-injury), motor-complete spinal cord injury (American Spinal Injury Association Impairment Scale A-B). Eight male TETRA wheelchair rugby players (34±5 years, C5-C7) and eight male PARA alpine skiers (35±5 years, T4-L3) were included in the study. Echocardiography was performed in the left lateral decubitus position and indices of left ventricular structure, global diastolic and systolic function, and mechanics were derived from the average across three cardiac cycles. Blood pressure was measured in the supine and seated positions. All results are presented as TETRA vs. PARA. There was no difference in left ventricular dimensions between TETRA and PARA. Additionally, indices of global diastolic function were similar between groups including isovolumetric relaxation time, early (E) and late (A) transmitral filling velocities and their ratio (E/A). While ejection fraction was similar between TETRA and PARA (59±4 % vs. 61±7 %, p=0.394), there was evidence of reduced global systolic function in TETRA including lower SV (62±9 ml vs. 71±6 ml, p=0.016) and cardiac output (3.5±0.6 L/min vs. 5.0±0.9 L/min, p=0.002). Despite this observation, both systolic and diastolic mechanics were maintained in TETRA, while several indices were lower in PARA including circumferential strain at the level of the papillary muscle (-23±4% vs. -15±6%, p=0.010) and apex (-36±10% vs. -23±5%, p=0.010) and their corresponding diastolic strain rates (papillary: 1.90±0.63 s-1 vs. 1.20±0.51 s-1, p=0.028; apex: 3.03±0.71 s-1 vs. 1.99±0.69 s-1, p=0.009). All blood pressures were lower in TETRA. The absence of an association between reduced global systolic function and mechanical dysfunction in either TETRA or PARA suggests any reductions in SV are likely attributed to impaired loading rather than inherent left ventricular dysfunction.